2018
DOI: 10.1177/1120672118757428
|View full text |Cite
|
Sign up to set email alerts
|

Ocular surface changes in recurrent pterygium cases post-operatively treated with 5-fluorouracil subconjunctival injections

Abstract: The cytology of ocular surface in recurrent pterygium is abnormal. After weekly intralesional 5-fluorouracil injections, it tends to normalize. The 5-fluorouracil compound is a safe and effective treatment to prevent pterygium recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“… 19 Another study assessed the changes in pathological parameters of the ocular surface before and after 10 intralesional injections of 5-FU in recurrent pterygium cases. 49 They reported an increase in the number of epithelial cells and density of goblet cells, reduction in the squamous metaplasia, and changing in abnormal cytology to normal in these injected eyes. Patients also reported lower conjunctival redness and less eye dryness after 5-FU injection.…”
Section: R Esultsmentioning
confidence: 89%
See 1 more Smart Citation
“… 19 Another study assessed the changes in pathological parameters of the ocular surface before and after 10 intralesional injections of 5-FU in recurrent pterygium cases. 49 They reported an increase in the number of epithelial cells and density of goblet cells, reduction in the squamous metaplasia, and changing in abnormal cytology to normal in these injected eyes. Patients also reported lower conjunctival redness and less eye dryness after 5-FU injection.…”
Section: R Esultsmentioning
confidence: 89%
“…The recovery of the conjunctival goblet cell population after CAU surgery in the pterygium may require more than 1 year. 49 Short durations of follow-up in most studies published before 2009 was a major limitation for the contribution of results in routine clinical practice. 7 15 17 44 50 Furthermore, since the loss to follow-up is common in the postoperative period, the validity of the reported recurrence rates is under debate.…”
Section: R Esultsmentioning
confidence: 99%
“…The presence of squamous metaplasia is, however, a problematic area, as the classical pathological knowledge conflicts with the current pterygium state-of-the-art. Multiple reports uniformly describe squamous metaplasia in pterygium [ 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 ]. Squamous metaplasia is known as the process by which a mature, non-squamous epithelium is replaced by a stratified, squamous epithelium ( Figure 3 D) [ 111 ].…”
Section: Uv-induced Cellular Reactionsmentioning
confidence: 99%
“…Grading systems for impression cytology—Four different systems have been published to evaluate the severity of metaplasia in impression cytology samples of pterygium: Murube and Rivas’s grading system [ 103 , 104 ], Nelson’s classification [ 106 ], Tseng’s grading system [ 110 ] and Wittpen’s grading system [ 109 ]. The criteria used for assessment are related to the nuclear/cellular morphology, epithelial cell size, nucleus-to-cytoplasmic ratio, cytoplasmic staining characteristics, goblet cell density, cellular organization and keratinization.…”
Section: Uv-induced Cellular Reactionsmentioning
confidence: 99%
“…found that eyes with pterygium showed markedly higher tear osmolarity levels, corneal staining, and conjunctiva redness scores, as well as lower tear break‐up time and tear volumes than the healthy fellow eyes (Ozsutcu et al., ). Two more recent studies also demonstrated the high prevalence of dry eye in patients with pterygium, and pterygium recurrence was found to be associated with a greater severity of dry eye, probably through perpetuating ocular surface inflammation in the postoperative period (Garcia Tirado, Boto de Los Bueis, & Rivas Jara, ; Tan, Vollmer‐Conna, Tat, & Coroneo, ). All of these studies implicated the potentially close relationship between pterygium and abnormal ocular surface function.…”
Section: Introductionmentioning
confidence: 94%